DETERMINASI PERBANKAN SYARIAH DI INDONESIA - Ariza Karina Putri; Beni Antomi; Putri Melisa; Tri Amar Prasetyo; Heni Noviarita (Business and Enterpreneurship Journal (BEJ), 2021)
The good performance of Islamic banking in Indonesia can result in advancing the national economy in Indonesia. Thus this study aims to find out how the determinants of Islamic banking performance influence and also to determine the effect of CAR, NPF, FDR, BOPO and NOM variables on ROA both partially and simultaneously during 2011-2016. This study uses panel data regression analysis. The research object consists of Islamic Commercial Banks in Indonesia with annual data from 2011 to 2016. The dependent variable (Y) used in panel data is ROA and the independent variable (X) consists of CAR, NPF, FDR, BOPO and NOM. shows that the variables affecting the profitability (ROA) of BUS during 2011- 2016, namely CAR, NPF and NOM have a significant positive effect on ROA, while FDR and BOPO have a significant negative effect on ROA. In addition, the CAR, NPF, FDR, BOPO, and